2017
DOI: 10.7860/jcdr/2017/29454.10546
|View full text |Cite
|
Sign up to set email alerts
|

An Alpha Fetoprotein Producing Gastric Tumor with Yolk Sac, Hepatoid and Papillary Adenocarcinoma Components

Abstract: A 75-year-old male presented with history of abdominal pain and generalised weakness for about three months. Clinically he was anaemic and per abdomen examination was unremarkable. Oesophagogastroduodenoscopy revealed an ulceroproliferative polypoidal growth involving the gastric antrum [Table/ Fig-1] and few scattered small sessile nodules in the body and antrum of stomach. Colonoscopy revealed a polyp in the rectum. The gastric antral lesion was biopsied and rectal polyp was excised and sent for histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In 1970, Bourreille et al proposed the concept of hepatoid adenocarcinoma (HAC) based on morphology and found that this subtype was often accompanied by elevated sAFP and more likely to have liver metastases [4,5]. Subsequent studies also found that gastric adenocarcinoma with enteroblastic differentiation (GAED) and yolk-sac tumor-like carcinoma had similar characteristics [6,7]. Successive studies concluded that regardless of whether there was a special pathological morphology, cases of positive AFP immunohistochemistry or elevated sAFP had a suggestive risk of progression, collectively referred to as "AFP-producing gastric adenocarcinoma" [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In 1970, Bourreille et al proposed the concept of hepatoid adenocarcinoma (HAC) based on morphology and found that this subtype was often accompanied by elevated sAFP and more likely to have liver metastases [4,5]. Subsequent studies also found that gastric adenocarcinoma with enteroblastic differentiation (GAED) and yolk-sac tumor-like carcinoma had similar characteristics [6,7]. Successive studies concluded that regardless of whether there was a special pathological morphology, cases of positive AFP immunohistochemistry or elevated sAFP had a suggestive risk of progression, collectively referred to as "AFP-producing gastric adenocarcinoma" [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 9 ] And in some AFP producing cases, the component of the tumor is not unique. [ 10 ] According to the literature, the incidence of AFP producing gastric cancer is 1.3% to 15%. [ 10 ] Above all, there is some clinical experience.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] According to the literature, the incidence of AFP producing gastric cancer is 1.3% to 15%. [ 10 ] Above all, there is some clinical experience. On one hand, gastric cancer without AFP producing cannot exclude the possibility of hepatoid adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%